If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + -7 = -3p + 7 Reorder the terms: -7 + 9p = -3p + 7 Reorder the terms: -7 + 9p = 7 + -3p Solving -7 + 9p = 7 + -3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3p' to each side of the equation. -7 + 9p + 3p = 7 + -3p + 3p Combine like terms: 9p + 3p = 12p -7 + 12p = 7 + -3p + 3p Combine like terms: -3p + 3p = 0 -7 + 12p = 7 + 0 -7 + 12p = 7 Add '7' to each side of the equation. -7 + 7 + 12p = 7 + 7 Combine like terms: -7 + 7 = 0 0 + 12p = 7 + 7 12p = 7 + 7 Combine like terms: 7 + 7 = 14 12p = 14 Divide each side by '12'. p = 1.166666667 Simplifying p = 1.166666667
| 9p-7=3p+7 | | 4x^3-24x^2-16=0 | | 32u=-7 | | 5x+23(x-4)=272 | | .12x+0.1(5000-x)=560 | | -7v=14 | | 4x^2+8x=y | | X-6x=0 | | 17x+17+102z= | | 5(90-7x)=x-26 | | 9p+13=4p-2 | | (x)(x^5)(x^4)= | | 17(x+1+6z)= | | -a=-34 | | 2+z=7 | | 1x-3=9x+3 | | 3x+10=2x+12 | | -2s=-72 | | -8a-6a= | | 13-s=50 | | y=3x^2+2x-5 | | 19+z=80 | | 0.05x=1760 | | 77-3x=15x+17 | | b-2x=(-6)-2(6) | | (6x+1)+x=4x+19 | | 4x+9=-107-7x | | (2-a)(2-a)-4=0 | | x+.23=24.60 | | 3-2y=(3y-2)-5y | | 7q+11=102 | | 14=3d-15+2a-6 |